The mGluR7 allosteric agonist AMN082 produces antidepressant-like effects by modulating glutamatergic signaling - Bradley, Stefania Risso; Uslaner, Jason M.; Flick, Rose B.; Lee, Ariel; Groover, Kristina M.; Hutson, Peter H. (Pharmacology, biochemistry and behavior, 2012)
Currently prescribed antidepressants affect the reuptake and/or metabolism of biogenic amines. Unfortunately for patients, these treatments require several weeks to produce significant symptom remission. However, recently it has been found that ketamine, a dissociative anesthetic agent that noncompetitively antagonizes NMDA (N-Methyl-d-aspartic acid) receptors, has rapid antidepressant effects at sub-anesthetic doses in clinically depressed patients. These findings indicate that modulation of the glutamatergic system could be an efficient way to achieve antidepressant activity. For this reason, other mechanisms influencing glutamatergic functioning have gained interest. For example, the metabotropic glutamate receptor 7 (mGluR7) allosteric agonist AMN082 (N,N′-dibenzyhydryl-ethane-1,2-diamine dihydrochloride) has been shown to be effective in the forced swim and tail-suspension test, behavioral assays sensitive to antidepressants. Here we extend the characterization of AMN082 by demonstrating its effects on differential reinforcement of low rates of responding (DRL)-30, another assay sensitive to antidepressants. Furthermore, we show the engagement of glutamatergic signaling by demonstrating the ability of the selective AMPA (2-amino-3-(5-methyl-3-oxo-1,2-oxazol-4-yl)propanoic acid) receptor antagonist NBQX (2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo[f]quinoxaline-2,3-dione) to reverse the effects of AMN082 in the tail suspension test. In contrast, NBQX failed to reverse the effects of imipramine in the same behavioral test. Finally, we report that behaviorally efficacious doses of AMN082 modulate phosphorylation of AMPA and NMDA receptor subunits in the hippocampus. These results suggest that the antidepressant-like effects of AMN082 are, at least in part, due to modulation of AMPA and NMDA receptor activity. Therefore, our findings confirm the hypothesis that mGluR7 could represent a novel target for treating depression. ► AMPA receptors are involved in the behavioral effects of mGluR7 agonist AMN082 administration. ► AMN082-induced decreased of immobility in the tail suspension test is attenuated by NBQX. ► AMN082 alters the phosphorylation of GluR1, NR1, NR2b subunits in the hippocampus. ► mGluR7 activation could be an alternative to NMDARs blockers in the treatment of mood disorders.